Global Labor Market Developments and Their Relation with HR Management - Ningsih, Supiah; Sipahutar, M Ali; Yusnandar, Willy; Sabrina, Sabrina; Syera, Inda Arfa (International Journal of Economics (IJEC), 2025)
Globalization has accelerated economic, social, and political integration between countries, creating an increasingly open and competitive labor market. This has encouraged the mobility of labor across countries, both physically and virtually, and expanded opportunities for individuals and companies to participate in the global economy. Technology, especially the digital revolution, artificial intelligence (AI), robotics, and automation, is a major driver of global labor market change. By 2030, more than 80% of global employers expect technology to revolutionize various industrial sectors and create high demand for new skills, such as programming, big data analysis, and technology literacy. Globalization has become a major factor changing the dynamics of labor markets around the world, including Indonesia. This development requires countries to adjust their labor market policies and structures to be able to compete amidst increasingly competitive and liberal global market pressures. One major trend is the implementation of a flexible labor market system, promoted by international institutions such as the World Bank and IMF in response to the incompatibility of rigid labor markets with global economic conditions. The development of the global labor market due to globalization has brought significant changes to the structure, behavior, and policies of the labor market, including in Indonesia. Human resource management is the key to managing these challenges and taking advantage of these opportunities, through adaptive, inclusive, and knowledge-based strategies to create competitive advantage and sustainable economic growth. The evolution of human resource management in the modern era is marked by digital transformation that changes the way organizations manage their workforce, from manual processes to automation and data-driven.